2019
DOI: 10.1007/s13592-019-00681-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of three sterol biosynthesis inhibiting fungicides on the toxicity of a pyrethroid and neonicotinoid insecticide to bumble bees

Abstract: Understanding how different pesticides influence bee health is inhibited by a limited knowledge about the interactions between different compounds to which bees are simultaneously exposed. Although research has demonstrated synergistic effects of some sterol biosynthesis inhibiting (SBI) fungicides on the toxicity of certain insecticides to bees, a high degree of variability exists in the relatively few SBI fungicide-insecticide interactions tested. Furthermore, most research has been conducted on honey bees, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…It is important to note that neonicotinoids show synergistic toxicity with certain fungicides that may be used simultaneously in agricultural settings. Thiamethoxam has been shown to have synergistic toxicity with myclobutanil (Iverson et al 2019) and imazalil (Raimets et al 2018), and clothianidin has been shown to act synergistically with propiconazole (Sgolastra et al 2017). Thus, although chronic exposure to field‐realistic concentrations of acetamiprid did not alter adult survival, microcolony development, or brood production, in combination with fungicides or other pesticides, acetamiprid may negatively affect growth and survival at a lower concentration.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that neonicotinoids show synergistic toxicity with certain fungicides that may be used simultaneously in agricultural settings. Thiamethoxam has been shown to have synergistic toxicity with myclobutanil (Iverson et al 2019) and imazalil (Raimets et al 2018), and clothianidin has been shown to act synergistically with propiconazole (Sgolastra et al 2017). Thus, although chronic exposure to field‐realistic concentrations of acetamiprid did not alter adult survival, microcolony development, or brood production, in combination with fungicides or other pesticides, acetamiprid may negatively affect growth and survival at a lower concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of pesticides tested for negative effects on bees have been insecticides. A smaller number of studies have measured the effects of fungicides on bee health, either alone or in combination with insecticides (Carnesecchi et al 2019;Iverson et al 2019). Certain fungicide and insecticide combinations are known to have synergistic effects, leading to increased toxicity to honey bees (Pilling et al 1995;Thompson and Wilkins 2003).…”
Section: Response To Pesticide Exposurementioning
confidence: 99%
“…An experimental design comparing the impact of oral consumption of insecticide + fungicide mixtures on three bee species (A. mellifera, B. terrestris, and Osmia bicornis) found a small but maintained increase in clothianidin toxicity when combined with propiconazole, which was especially pronounced for the two non-Apis species with an almost three-fold increase for O. bicornis (Robinson et al, 2017). In a similar study, contact exposure of insecticides + fungicides, approximating LD 20 values and maximum sublethal levels, respectively, resulted in synergistic toxicity to B. impatiens workers (Iverson et al, 2019). Specifically, a synergistic interaction was noted for the triazole SBI fungicide difenoconazole when mixed with the pyrethroid bifenthrin, resulting in a maximum synergy ratio of 1.48.…”
Section: Non-apis Bees (Bombus and Solitary Species)mentioning
confidence: 75%
“…Since they are often applied in agricultural crop production systems throughout the year, including periods of bloom (Bosch and Blas, 1994;Andert et al, 2016;Zubrod et al, 2019;Heller et al, 2020), Apis and non-Apis bee species can come into contact with these chemicals while actively pollinating. Simulating these scenarios, laboratory, and semi-field studies have demonstrated the impacts of fungicide and herbicide exposure (as both single chemicals and in combination with other pesticides) on lethal and sublethal toxicity to different species of managed bees (Fisher et al, 2017;Heard et al, 2017;Iverson et al, 2019). Several recent studies have also linked physiological changes at the molecular and the genetic levels in bees after exposure to these agricultural chemicals (Jumarie et al, 2017;Mao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%